SITUATIONAL ANXIETY IN L2 INSTRUCTION: A CASE STUDY ON LEARNER VIRTUAL BEHAVIOUR - Plastina, Anna Franca (ELIA: Estudios de Lingüística Inglesa Aplicada, 2017)
Abstract Besides motivation and attitude, anxiety proves to strongly affect L2 learning. Synchronous text-based environments offer an opportunity to investigate situational anxiety in a learning environment which differs from the traditional classroom. In catering differently to factors such as personality trait, acceptance, orientation, communication, performance and evaluation, virtual learning spaces may alter users’ behaviour and situational anxiety.This paper reports on a small-scale case study carried out with EFL tertiary learners at the Language Centre, University of Calabria, Italy and in-service teachers training at the local chapter of TESOL-Italy. Under different circumstances and for different purposes, both groups were sharing the common ground of approaching virtual learning environments as novices. Findings reflect on comparative L2 situational anxiety in relation to virtual behaviour.